Prediction of 10-Year Risk of Cardiovascular Disease among Diabetic Patients in Bangladesh - Akter, Nazma (Delta Medical College Journal, 2022)
Background: Diabetic populations and people from developing countries have a higher risk of developing CVD than the general population. Bangladesh, a rapidly developing country, faces progressive urbanization and the adoption of a westernized lifestyle, factors which contribute to the rising burden of cardiovascular disease. Objective: To predict the risk of developing cardiovascular diseases among diabetic patients in Bangladesh. Materials and method: This cross sectional study was done among the diabetic patients attending the outpatient department of MARKS Medical College &Hospital, Dhaka, Bangladesh from February 2018 to July 2018. Patients suffering from any cardiovascular disease were excluded from the study. The purpose of the study was explained and informed written consent was obtained from each subject who volunteered for the study. Data was collected with a pre tested structured questionnaire. Cardiovascular risk was assessed based on Framingham scoring, calculated by using online calculator and expressed as percentages. Based on the total risk score calculated, subjects were categorized to be at high (≥20%), intermediate (10-19%), and low (<10%) risk of cardiovascular disease. Data analysis was done in SPSS software version 16. Result: Among the diabetic patients, 32.62% are in high and 22.64% are in intermediate risk category based on Framingham scoring system for developing cardiovascular disease. A statistically significant association was found between cardiovascular risk and factors like gender, occupational status, smoking and hypertension. Conclusion: This study reveals that the diabetic populations are at higher risk of developing cardiovascular diseases. Hence awareness about the risk should be created and appropriate intervention at early stages should be implemented at primary health care level. Delta Med Col J. Jul 2020 8(1): 32-40